Komisi I DPR-RI dengan Pangdan [i.e. Pangdam] Jaya tgl. 10 Pebruari 1994 tahun sidang 1993-1994 (Dewan Perwakilan Rakyat, Republik Indonesia, 1994)
Security issues in Jakarta and its surroundings; report of a meeting of the 1st Commission of the Indonesian Parliament.